Analisis Butir Soal Pada Buku Ajar Matematika SMP Kelas VII Kurikulum 2013 (Edisi Revisi 2016) Ditinjau Dari Aspek Kognitif Timss - Anindyarini, Rosyita; , Prof. Dr. Budi Murtiyasa, M.Kom (2017)
This study aimed to analyze the questios in the textbook of mathematics for the seven-grade level of Junior High School revised edition 2016 of curriculum 2013 which reviewed from cognitive aspect based on TIMSS 2015. Cognitive aspect based on TIMSS 2015 including knowing, applying, and reasoning. So that, chosen the textbook of mathematics for the seven-grade level of Junior High School revised edition 2016 of curriculum 2013 which has been published by Culture and Education Ministry. This study implemented by analyzing descriptively the items in the textbook which reviewed from cognitive aspect of TIMSS 2015. The results of research suggest that: (1) in the textbook, there are 287 quetions or with the percentage 14% including on knowing aspect. The proportion is not full fill 6,86% of TIMSS's rule becasue knowing aspect of TIMSS 2015 have 35%. (2) There are 404 quetions or with the percentage 39,41% including on applying aspect. The proportion is not full fill 0,39% of TIMSS's rule because applying aspect of TIMSS 2015 HAVE 40%. (3) There are 326 questions or with the percentage 31,96% including on reasoning aspect. The porportion have excess 6,96% of TIMSS's rule because reasoning aspect of TIMSS 2015 have 25%. The conclusion of research is there are differences quantity of cognitive aspect between the textbook and TIMSS 2015. So, this textbook is not good and can not be the main textbooks for students to exercise. The textbook of mathematics should be revised continually in order to increase education quality in Indonesia. Keyword: cognitive aspect, textbook, question